Training of Light Industry workers in Uzbekistan war and Post-War Years - Akromova Fazilat (Researchparks Publishing, 2022)
On August 16, 1941, the Central Committee of the CPSU (b) and the Council of People's Commissars of the USSR approved the prepared document. State plan of the USSR military and economic plan for the fourth quarter of 1941 and for 1942 for the regions of the Volga region, the Urals, Western Siberia, Kazakhstan and Central Asia. This plan was an extensive program for completing the transition of the national economy to military rails, a sharp increase in the output of defense products, the full development of heavy industry, the creation of new industrial centers. This article provides information about light industry workers in Uzbekistan during the Second World War.